Characterization of the radiative heating stage in the end-forming process of PVC pipes. (September 2018) - Lucchi, M.; Lorenzini, M.
Highlights: The transient heating stage of the end-forming process was studied numerically. Temperature unevenness due to pipe geometry and angular velocity was quantified. A 1D finite-element model to simulate surface temperature control was implemented. The models allow complete characterization of the heating stage of end-forming. Abstract: The end-forming of polyvinyl chloride (PVC) pipes is a manufacturing process aimed at deforming one end of a tube to allow connections between pipes. The deformation is preceded by a heating stage which leads to softening of the material and which, if not properly carried out, may cause unacceptable defects in the final product. The heating stage in the end-forming process often occurs within ovens equipped with infrared short-wave (SW) lamps, favoring the penetration of thermal radiation into the material. The lamps are placed at certain angular positions, making it necessary to impose a rotary motion to the pipe, to allow a circumferentially uniform heating. In this work a transient analysis of the end-forming heating stage has been conducted by means of two finite-element models, creating a design tool for the complete characterization of the process. The first model makes use of a time-dependent heat generation term which takes into account the actual heat flux distribution incident at the outer surface of the pipe, leading to the identification of suitable angular velocities to achieve uniform heating. In the second model, a local temperature control has been introduced in order to characterize the process in terms of heating time. To the best authors' knowledge, this is the first numerical instrument able to completely characterize the heating stage of the end-forming process of PVC pipes.